Economic impact of combined torrefaction and pelletization processes on forestry biomass supply. Issue 4 (16th July 2016) - Li, Yuanzhe; Tittmann, Peter; Parker, Nathan; Jenkins, Bryan
Abstract: The cost of supplying wood biomass from forestry operations in remote areas has been an obstacle to expansion of forest‐based bioenergy in much of the western United States. Economies of scale in the production of liquid fuels from lignocellulosic biomass feedstocks favor large centralized biorefineries. Increasing transportation efficiency through torrefaction and pelletization at distributed satellite facilities may serve as a means to expand the utilization of forestry residuals in biofuel production. To investigate this potential, a mixed‐integer linear program was developed to optimize the feedstock supply chain design with and without distributed pretreatment. The model uses techno‐economic assessment of scale‐dependent biomass pretreatment processes from existing literature and multimodal biomass transportation cost evaluations derived from a spatially explicit network analysis as input. In addition, the sensitivity of the optimal system configuration was determined for variations of key input parameters including the production scale of pretreatment facilities, road and rail transportation costs, and feedstock procurement costs. Torrefaction and densification were found to reduce transportation costs by $0.84 per GJ and overall delivered costs by $0.24 per GJ, representing 14.5% and 5.2% cost reductions compared to feedstock collection without pretreatment. Significant uncertainties remain in terms of the costs associated with deploying torrefaction equipment at the scales modeled, but the level of potential cost savings suggests further analysis and development of these alternatives.